Analysis and evaluation of the websites of selected online bookstores. - Pang, Shoo Hoon. (2008)
The study examines the salient features of the websites of selected online bookstores and evaluates their effectiveness in promoting books sales. In addition, a survey of the libraries of tertiary academic institutions in Singapore was conducted to determine their use of online bookstores and the useful features in selecting materials.